Exploring The Potentials and Drawbacks of Hysteresis Current Controller For SRM: A Case Study Of Wind Energy Conversion System - Kabir, Imamuddeen; Jibril, Yusuf; Sa'idu Abubakar, Adamu; Abidemi Olarinoye, Gbenga (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2024)
Switched Reluctance Machines (SRMs) have drawn interest in renewable energy systems because of their special qualities and applicability. This study examines the idea of hysteresis current regulation in a wind energy conversion system with a Switched Reluctance Generator (SRG). The system is modeled in MATLAB/SIMULINK. The model is simulated and analyzed to ascertain the system’s benefits and shortcomings, focusing on reducing torque ripples in SRG. Considering most classical controllers are complicated to construct, the hysteresis current control is straightforward and effective. However, this controller's two primary shortcomings are that it produces a variable switching frequency and increases current ripples at a steady state, both enhancing acoustic noise in SRM. Lastly, the report suggests that improving controller performance should be the primary emphasis of future research in this field.